Knowledge and Behaviour Regarding Heart Disease Prevention in Chinese Canadian Immigrants - Hislop, T. Gregory (Can J Public Health, 2008)
OBJECTIVE: Although Chinese are one of the fastest growing minorities in Canada, there is little information about heart disease prevention behaviour in Chinese immigrants. Our objective was to examine the knowledge and practices of Chinese immigrants regarding heart disease prevention. METHODS: 504 randomly selected Chinese adult immigrants participated in a community-based, in-person survey in Vancouver during 2005. The survey included questions on heart disease prevention knowledge and practices. RESULTS: Although respondents were quite knowledgeable about heart disease risk factors, their behaviours to reduce heart disease risk were generally low. Thirteen percent of respondents consumed five or more servings of fruit/vegetables per day; 37% engaged in regular physical activity; 54% never used tobacco; 81% had received a blood pressure check in the past 2 years; and 54% had received a cholesterol test in the past 5 years. Differences were found in these behaviours by gender, age, English fluency, birth country and duration of residence in North America. The associations are presented between these demographic variables and heart disease prevention behaviours. CONCLUSION: Heart disease prevention programs are needed in Chinese immigrant populations, especially aimed at increasing fruit/vegetable consumption and regular physical activity. Efforts are also needed to decrease tobacco use and to increase cholesterol testing.